EFFICACY OF UTERINE PACKING AND INTRAUTERINE BALLOON TAMPONADE IN ATONIC POSTPARTUM HEMORRHAGE COMPARISON - KHAN , N; ALI , K (Biological and Clinical Sciences Research Journal, 2023)
A randomized controlled trial was conducted between March 1, 2023, and September 1, 2023, at the Gynae unit of the Mardan Hospital complex in Mardan. The study aimed to evaluate the effectiveness of two strategies in treating postpartum hemorrhage caused by atony. The two strategies evaluated were uterine gauze packing and uterine balloon tamponade. A total of 168 women who had experienced postpartum hemorrhage due to uterine atony after a vaginal birth were enrolled in the study through non-probability sampling. Patients with clotting disorders, trauma-related hemorrhage, and those who had undergone cesarean deliveries were excluded from the study. The study had two groups of patients, with 84 patients enrolled in group A and 84 in group B. The study aimed to compare the effectiveness of the two strategies in minimizing blood loss in the first 24 hours following birth. The study found that uterine balloon tamponade was more effective in reducing postpartum hemorrhage caused by uterine atony than uterine gauze packing. Specifically, 75 (89.3%) patients in group A reported the effectiveness of uterine balloon tamponade, while uterine gauze packing was reported in 61 (72.6%) patients in group B. This difference in effectiveness was statistically significant (P=0.006). The Chi-square test was used to compare the two groups, with a P value of 0.05 considered significant. In conclusion, the study suggests that uterine balloon tamponade is more effective in reducing postpartum hemorrhage caused by uterine atony than uterine gauze packing.